Triiodothyronine (T3) does not induce RANKL expression in rat ROS 17/2.8 cells - Saraiva, Patricia R. [UNESP]; Teixeira, Silvania S. [UNESP]; Nogueira, Célia Regina [UNESP]; Padovani, Carlos Roberto [UNESP] (Sbem-soc Brasil Endocrinologia & Metabologia, 2008)
Osteoclastogenesis may be regulated via activation of the RANK/RANKL (receptor activator of nuclear factor-kappa B/ receptor activator of nuclear factor-kappa B ligand) system, which is mediated by osteoblasts. However, the bone loss mechanism induced by T3 (triiodothyronine) is still controversial. In this study, osteoblastic lineage rat cells (ROS 17/2.8) were treated with T3 (10(-8) M 10(-9) 10 M, and 10(-10) M), and RANKL mRNA (messenger RNA) expression was measured by semiquantitative RT-PCR. Our results show that T3 concentrations used did not significantly enhance RANKL expression compared to controls without hormone treatment. This data suggests that other mechanisms, unrelated to the RANK/RANKL system, might be to activate osteoclast differentiation in these cells.

A osteoclastogênese pode ser regulada via ativação do sistema RANK/RANKL (receptor ativador do fator nuclear kapa B/ ligante do receptor do fator nuclear kapa B), que é mediado pelos osteoblastos. Entretanto, o mecanismo de perda óssea induzido pelo T3 (triiodotironina) ainda é controverso. Neste estudo, a linhagem osteoblástica de células de rato ROS 17/2.8 foi tratada com T3 (10-8 M, 10-9 M e 10-10 M), e a expressão do mRNA do RANKL foi medida por RT-PCR semiquantitativo. Nossos resultados mostraram que as concentrações de T3 utilizadas não induziram significativamente a expressão do RANKL, comparado ao controle (sem tratamento hormonal). Estes dados sugerem que outros mecanismos, não relacionados ao sistema RANK/RANKL, são usados para ativar a diferenciação osteoclástica nestas células.
Triiodotironina (T3) não induz a expressão de Rankl em células de rato ROS 17/2.8
Keywords: thyroid hormone; RANKL; bone; rat; ROS17/2.8 cell